The relationship between metabolic syndrome, its components, and dry eye: A cross-sectional study - Karaman Erdur, Sevil; Aydın, Rukiye; Özsütçü, Mustafa; Olmuşçelik, Oktay; Eliaçık, Mustafa; Demirci, Göktuğ; Kocabora, Mehmet Selim (Tayor & Francis Inc, 2017)
Purpose: The aim of this study was to evaluate tear osmolarity and tear film function and ocular surface changes in patients with metabolic syndrome.Methods: 108 eyes of 64 patients with metabolic syndrome (group 1) and 110 eyes of 55 healthy individuals (group 2) were included in this cross-sectional study. All participants were evaluated using the Ocular Surface Disease Index (OSDI) questionnaire, Schirmer I test, tear film break-up time (TBUT), and tear osmolarity. Main outcome measures were Ocular Surface Disease Index (OSDI) questionnaire, Schirmer I test, tear film break-up time (TBUT), and tear osmolarity values.Results: Tear osmolarity values and OSDI scores were significantly higher in group 1 (314.4 19.1 mOsm and 38.9 +/- 1.1, respectively) compared with group 2 (295 +/- 14.3 mOsm and 18.69 +/- 17.2, respectively) (p = 0.01 for both). The Schirmer test values and TBUT in group 1 (10 +/- 3.7 mm and 14.8 +/- 3.6 sec, respectively) were significantly lower compared with group 2 (16.8 +/- 2.6 mm and 18.1 +/- 0.5 sec, respectively) (p < 0.001 for both). There was significant correlation between tear osmolarity versus waist circumference and fasting blood glucose in the study group (r = 0.364, p = 0.04; and r = 0.542, p 0.001, respectively).Conclusions: This study showed that metabolic syndrome can influence tear osmolarity and tear film function. Patients with metabolic syndrome showed tear hyperosmolarity and tear film dysfunction.
WOS: 000407080800005
PubMed ID: 28328296
Keywords: Dry Eye; Metabolic Syndrome; Schirmer Test; Tear Osmolarity; Tear Film